Dual-Polarized Cross Bowtie Dipole for 3G and LTE Applications - Zhi-Ya Zhang; Jia-Yue Zhao; Qiongqiong Liu; Guang Fu (International Journal of Antennas and Propagation)
A dual-polarized cross bowtie dipole element with parasitical circular patch and vertical metal cylinders for base station antennas is presented. A pair of orthogonal cross bowtie dipoles, with a reflector ground plane, is used to obtain the two linear polarizations. Besides two inverted L-shaped feed strips and two shorted feed baluns, parasitical circular patch is introduced to improve the impendence bandwidth and vertical metal cylinders are employed to decrease the lateral dimensions of the antenna. A wideband impedance characteristic of about 45.6% for VSWR ≤ 1.5 (+45° polarization) and VSWR ≤ 1.5 (−45° polarization) ranging from 1.76 to 2.80 GHz is obtained. Moreover, the stable peak gain, unidirectional radiation patterns, high isolation between the two orthogonal polarizations, and low cross-polarization over the whole operating band are also achieved. The proposed antenna is very suitable for potential base station applications in mobile communication such as TD-SCDMA, WCDMA, and CDMA2000 and LTE applications.